G-Portal : a map-based digital library for distributed geospatial and georeferenced resources - Lim, Ee Peng (2011)
As the World Wide Web evolves into an immense information network, it is tempting to build new digital library services and expand existing digital library services to make use of web content. In this paper, we present the design and implementation of G-Portal, a web portal that aims to provide digital library services over geospatial and georeferenced content found on the World Wide Web. G-Portal adopts a map-based user interface to visualize and manipulate the distributed geospatial and georeferenced content. Annotation capabilities are supported, allowing users to contribute geospatial and georeferenced objects as well as their associated metadata. The other features included in G-Portal's design are query support, content classification, and content maintenance. This paper will mainly focus on the architecture design, visualization and annotation capabilities of G-Portal.